Concert orchetral folio no.1 - Zamecnik, J.S. (Sam Fox Pub., 1917)
AtonementnThe dancer of NavarrenEcstacynBon VivantnTearsnEgyptianA Dutch WindmillnThe Wooing hournReve D'amournNeapolitan nightnMen of SpartanBallet sentimental